Climate change and the socioeconomics of global food production: a quantitative analysis of how socioeconomic factors influence the vulnerability of grain crops to drought - Simelton, Elisabeth; Fraser EDG; Termansen, Mette; Benton, Tim G.; Gosling SN; South A; Arnell, N.W.; Challinor, Andrew J.; Dougill, Andrew J.; Forster PM (Centre for Climate Change Economics and Policy, 2010)
The impact of climate change on agriculture depends on the environmental and socio-economic contexts in which the changes occur. However, current tools to anticipate climate change impacts focus almost entirely on biological and environmental processes. For example, most large-scale crop models can identify where yields are sensitive to new temperatures and CO2 concentrations but do not include any socio-economic factors that may enable (or inhibit) farmers’ abilities to adapt. To address this gap, this paper uses national scale socio-economic, meteorological and agricultural data to identify socio-economic factors that have made rice, maize and wheat production resilient and sensitive to past droughts. Results suggest that cereal harvests in countries undergoing economic and political transition are most vulnerable to droughts and that factors related to investments in the agriculture sector (such as the amount of fertilizer used by farmers or the amount of Gross Domestic Product produced by a nation’s agricultural sector) help reduce vulnerability. While results are limited by data quality and availability, this study provides preliminary quantitative insights that highlight important areas for further research on the socio-economic factors that create vulnerability to climate change.